PEMBERDAYAAN MASYARAKAT DESA BERBASIS NILAI-NILAI TAUHID DI DESA KARANG TENGAH DAN DESA CIJAYANTI KECAMATAN BABAKAN MADANG KABUPATEN BOGOR (Studi Pada Ukm Snack Polubi dan Bumdes Cipta mandiri) - Ismartaya Ismartaya; Ahmad Ripai; Dicky Muhammad; Erby Nugraha; Faizal Naufalnadhir; Ilhamy Satriawan; Mohammad Rizky Fadly; Nada Fauziah Salsabillah; Nurul izzah (LP2M STP Mataram, 2021)
This research has been done at fvillage of central karang tengah and cijayanti village. It aims to: (a) identify industrial profile; (b) identify entrepreneur characteristics; (c) measure the level of business success; (d) test and analyze entrepreneur’s characteristic influence (Personal Ability and Social Ability) to the level of business success; and (e) find variable which has dominant effect on business success. Research was done by using survey design. Primary data are obtained through questionnaires methods, observation and interview. Secondary data are obtained by using documentation method. Census method is used as sampling method with consideration of population amount is small. This research conclude that: (a) Level of business success is considerably good as shown on stable sale trend and improvement; (b) Independent variables which consist of Personal ability and Social Ability simultaneously have significant effect on business success; (c) Social ability variable have significant effect on level of business success. While Personal Ability variable doesn't has significant effect on level of business success. Social ability has dominant influence to level of business success.